Impact Of Revocation Of Oil Fuel Subsidies In Accordance With The Concept Of Good Governance - Ila Karmila (Journal of Bussines Management Basic, 2022)
The essence of this research is to find out the impact of revocation of fuel subsidies in accordance with the concept of good governance as an effort to divert fuel subsidies from consumptive to productive. For the price increase, the government will prepare a compensation fund distribution scheme using electronic money. This assistance is realized through the distribution of Healthy Indonesia Cards (KIS), Smart Indonesia Cards (KIP), and Prosperous Family Cards (KKS). The distribution of compensation funds is a form of effort to implement President Joko Widodo's vision. However, KIS, KIP and KKS assistance is still questionable where the budget comes from. The implementation did not consult with the DPR and did not provide an explanation to the public where the funds for the cards came from. This ignores the principles of Good Governance or good governance, even though it is the prerogative of the President, but the mechanism adopted is less transparent and accountable. In the end, Pratikno (Minister of State Secretary) answered the criticism over the cost of issuing KIS, KIP and KKS. The budget for the issuance of all these cards comes from the BUMN Corporate Social Responsibility (CSR), which is only temporary, but for the following year, the procurement of KIS, KIP, and KKS will be included in the APBN. In fact, Pratikno recommends that the most important thing right now is to focus on the smooth implementation of the KIS, KIP, and KKS programs. the planning, implementation and evaluation stages are needed in the KIS, KIP and KKS programs for compensation for the increase in fuel prices, so it is not only the implementation that is carried out but the evaluation must also be carried out properly. If the planning, implementation and evaluation are not implemented or fail, then later it will be a futile program and only a waste of state money. It would be even better if the policy touched impact and did not stagnate in output or outcome. This can be done through the official website in the form of information so that the public can access it easily